This baby is not for turning: Women's experiences of attempted external cephalic version. Issue 1 (December 2016) - Watts, N.; Petrovska, K.; Bisits, A.; Catling, C.; Homer, C.
Abstract Background Existing studies regarding women's experiences surrounding an External Cephalic Version (ECV) report on women who have a persistent breech post ECV and give birth by caesarean section, or on women who had successful ECVs and plan for a vaginal birth. There is a paucity of understanding about the experience of women who attempt an ECV then plan a vaginal breech birth when their baby remains breech. The aim of this study was to examine women's experience of an ECV which resulted in a persistent breech presentation. Methods A qualitative descriptive exploratory design was undertaken. In-depth semi-structured interviews were conducted and analysed thematically. Results Twenty two (n  = 22) women who attempted an ECV and subsequently planned a vaginal breech birth participated. Twelve women had a vaginal breech birth (55 %) and 10 (45 %) gave birth by caesarean section. In relation to the ECV, there were five main themes identified: 'seeking an alternative', 'needing information', 'recounting the ECV experience', 'reacting to the unsuccessful ECV' and, 'reflecting on the value of an ECV'. Conclusions ECV should form part of a range of options provided to women, rather than a default procedure for management of the term breech. For motivated women who fit the safe criteria for vaginal breech birth, not being subjected to a painful experience (ECV) may be optimal. Women should be supported to access services that support vaginal breech birth if this is their choice, and continuity of care should be standard practice.